DEVELOPING VIDEO BLOG AS TEACHING MEDIA IN SPEAKING OF REPORT TEXT FOR GRADE XI VOCATIONAL HIGH SCHOOL - Triwananda Triwananda; Sumarsih Sumarsih; Anggraini Thesisia Saragih (Universitas Negeri Medan, 2018)
This study aimed to develop Video Blog as Teaching Media for Students of Multimedia Programme. This study was conducted by using Research and Development (R & D).Instruments for collecting data were syllabus, questionnaire and interview. The data was gathered by administering interview to the teacher and distributing questionnaires to the students. The result of this study was developed Video Blog which contained explanation, students’ activities and the example of report text in spoken.The average scores of media’s assesment were 4.04 from English teacher and 4.56 from English lecturer. It means the developed Video Blog as Teaching Media were categorized as very good or very appropriate for students of Multimedia Programme. Key words: Report text, Research and Development (R&D), Report Text